2013
DOI: 10.1063/1.4797497
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation-induced saline Rayleigh convection inside a colloidal droplet

Abstract: Inside evaporating two-component sessile droplets, a family of the Rayleigh convection exists, driven by salinity gradient formed by evaporation of solvent and solute. In this work, the characteristic of the flow inside an axisymmetric droplet is investigated. A stretched coordinate system is employed to account for the effect of boundary movement. A scaling analysis shows that the flow velocity is proportional to the (salinity) Rayleigh number (Ras) at the small-Rayleigh-number limit. A numerical analysis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 42 publications
6
56
0
1
Order By: Relevance
“…[14]). Yet, even an initially uniform concentration profile will create a gradient due to evaporation, so the present definition is more useful here, and was adopted by Kang et al [6]. The problem analyzed in this section is a laterally infinite two-dimensional cuvette filled with a saline solution.…”
Section: Linear Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[14]). Yet, even an initially uniform concentration profile will create a gradient due to evaporation, so the present definition is more useful here, and was adopted by Kang et al [6]. The problem analyzed in this section is a laterally infinite two-dimensional cuvette filled with a saline solution.…”
Section: Linear Stability Analysismentioning
confidence: 99%
“…The physical parameters used to solve the linear system are shown in Table II. The value of β was taken from Kang et al [6], and the evaporation speed was measured experimentally.…”
Section: Numerical Implementationmentioning
confidence: 99%
“…A study of the effect of saline Rayleigh convection on an evaporating sessile drop deposited on a nonsoluble substrate was recently carried out by Kang et al (2013). The authors investigated the evaporation dynamics using NaCl aqueous drops on a hydrophobic smooth substrate and showed that the evaporation-induced density gradient affects the evaporation dynamics.…”
Section: Evaporation In Presence Of Solute Concentration With or Withmentioning
confidence: 99%
“…Reproduced with permission fromKang et al (2013). The left half of the plane is for the concentration distribution, and the right half of the plane is for the velocity field.…”
mentioning
confidence: 99%
“…For instance, Kang et al (2013) investigated the evaporation-induced Rayleigh and Marangoni convections on the vertical cross-sectional plane in a sessile droplet. They used fluorescent particles and a cutoff filter to avoid laser light reflections, which may deteriorate image quality and alleviate the uncertainty.…”
Section: Introductionmentioning
confidence: 99%